High-thermal-conductivity aluminum-based copper-clad plate and preparation method thereof

By using functional components and modified thermal fillers in the insulating base layer of aluminum-based copper clad plate, the problems of processing difficulties and reduced insulation performance caused by the improvement of thermal conductivity of the insulating base layer in the prior art are solved, and high thermal conductivity and insulation performance are achieved Take into account both.

CN119459051AActive Publication Date: 2025-02-18HENAN ACAD OF SCI INST OF APPLIED PHYSICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411679629.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

When the existing aluminum-based copper clad plate improves the thermal conductivity of the insulating base layer, it is easy to cause processing difficulties, reduce mechanical properties and adhesive properties, and affect the insulation properties.

Method used

Using functional components and modified thermal fillers, the thermal conductivity and insulation of thermal glue solution are improved through the combination of microcrystalline cellulose structure, ricinoleate structure and pyridyl group, and the thermal conductivity and octene of boron nitride Chemical bonding of plasmic succinic anhydride enhances the dispersion and loading capacity of thermally conductive fillers.

Benefits of technology

While achieving high thermal conductivity and insulation performance of aluminum-based copper clad plate, it improves the processing convenience and mechanical properties of the plate, and avoids the reduction of insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad plate preparation, and particularly discloses a high-thermal-conductivity aluminum-based copper-clad plate and a preparation method thereof.The high-thermal-conductivity aluminum-based copper-clad plate comprises an aluminum-based bottom plate and a prepreg, and the prepreg is prepared by thermally curing a heat-conducting glue solution and a copper foil; the added heat-conducting glue solution contains a functional component and a modified heat-conducting filler, the functional component contains a microcrystalline cellulose structure, a ricinoleate structure and pyridyl, and due to the existence of the microcrystalline cellulose structure, on one hand, the high crystallinity and orientation of the functional component are exerted, and on the other hand, the microcrystalline cellulose structure can form hydrogen-bond interaction with the modified heat-conducting filler, so that the heat-conducting property of the functional component is improved; the ricinoleate structure has orderliness, pyridyl can generate pi-pi interaction with a benzene ring on the modified heat-conducting filler, and due to the existence of the modified heat-conducting filler, on one hand, good heat conductivity of boron nitride is exerted, and on the other hand, octenyl succinic anhydride grafted on the modified heat-conducting filler can generate chemical bonding with sulfydryl on the functional component, so that the heat conductivity of boron nitride is improved. Through the synergistic effect of all the structures, the thermal conductivity and the insulating property of the aluminum-based copper-clad plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper clad laminate preparation, and more specifically, to a high thermal conductivity aluminum-based copper clad laminate and a preparation method thereof. Background Art

[0002] Aluminum-based copper-clad laminate is a plate-shaped material made of electronic glass fiber cloth or other reinforcing materials impregnated with resin, single resin, etc. as an insulating adhesive layer, covered with copper foil on one or both sides and hot-pressed. It has good heat dissipation performance, mechanical strength and electrical properties, and is an ideal material for manufacturing high-performance PCBs.

[0003] As a substrate material for printed circuit boards, copper clad laminates must have a certain thermal conductivity to meet the needs of electronic products. Conventional copper clad laminates are composed of insulating base layers, metal base layers, copper foils, etc., among which metal base layers and copper foils generally have good thermal conductivity. To achieve the thermal conductivity of copper clad laminates, it is necessary to start with improving the thermal conductivity of the insulating base layer. In the prior art, in order to improve the thermal conductivity of the insulating base layer, the amount of thermally conductive particles is often increased. However, the modified thermally conductive filler has a small molecular weight and cannot participate in the curing reaction. It is easy to migrate and precipitate, which makes the insulating base layer difficult to process, and the mechanical properties and bonding properties of the prepared insulating base layer are reduced, which ultimately affects the insulation performance of the copper clad laminate. Therefore, providing an aluminum-based copper clad laminate with good thermal conductivity and excellent insulation performance is a technical problem that needs to be solved at present. Summary of the invention

[0004] In order to solve the problems mentioned in the above background technology, the present application provides a high thermal conductivity aluminum-based copper clad laminate and a preparation method thereof.

[0005] A high thermal conductivity aluminum-based copper-clad laminate comprises an aluminum-based substrate and a prepreg, wherein the prepreg is made by thermally curing a thermally conductive adhesive and copper foil.

[0006] The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermal conductive adhesive on the copper foil, controlling the adhesive coating line speed to 12-20 m / min, controlling the coating thickness to 75-95 μm, and heat treating at 230-260° C. for 2-4 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20-25 MPa and 280-320° C. for 1.8-2.2 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0007] Preferably, the method for preparing the thermally conductive adhesive comprises the following steps: Step 1: prepare the following raw materials by weight: 64-132 parts of bisphenol A epoxy resin, 16-30 parts of functional components, 8-18 parts of modified thermal conductive filler, 20-40 parts of organic solvent, 0.1-0.2 parts of photoinitiator, 25-30 parts of curing agent, and 1-5 parts of curing accelerator; The second step is to add the functional components, modified thermal conductive filler and photoinitiator into the organic solvent, stir evenly, irradiate with ultraviolet light for 10-20 minutes, control the irradiation temperature at 50-56°C, cool down to 25-30°C, and then add bisphenol A type epoxy resin, curing agent and curing accelerator in sequence, emulsify for 1.6-2.8 hours, and let stand for 5-7 hours to obtain the thermal conductive adhesive liquid.

[0008] Preferably, the photoinitiator is dimethyl benzoate.

[0009] Preferably, the organic solvent is one or more of propylene glycol methyl ether, propylene glycol methyl ether acetate and cyclohexanone mixed in any proportion.

[0010] Preferably, the curing agent is epoxy resin curing agent T31.

[0011] Preferably, the curing accelerator is one or more of 1-benzylbenzene-2-ethylimidazole, 2-ethyl-4-methylimidazole and 1-cyanoethylimidazole mixed in any proportion.

[0012] Preferably, the method for preparing the functional component comprises the following steps: Step A1, mix microcrystalline cellulose and saturated sodium hydroxide solution evenly, then add epichlorohydrin, heat to 58-64°C, continue stirring for 5.2-6.4h, filter, then add a mixture of ricinoleic acid, pyridine and anhydrous DMF dropwise, control the dripping within 30min, heat to 76-82°C, continue the reaction for 4-6h, filter, wash and dry to obtain a hydroxyl monomer, wherein microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a are added dropwise. The mass ratio of the mixed liquid a is 0.6-1.0:64-76:2.4-3.0:32-34. In the mixed liquid a, the mass ratio of ricinoleic acid, pyridine and anhydrous DMF is 4:0.03-0.05:28-30. In the above reaction process, under alkaline conditions, the hydroxyl groups on the surface of microcrystalline cellulose undergo a substitution reaction with epichlorohydrin, and the epoxy groups on the surface of the substituted microcrystalline cellulose continue to undergo a ring-opening esterification reaction with ricinoleic acid under the catalysis of pyridine to obtain a hydroxyl monomer. Step A2, adding hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid to anhydrous DMF, stirring evenly, heating to 74-80°C under nitrogen protection, stirring for reaction for 9-12h, filtering after the reaction, washing, and drying to obtain functional components, wherein the mass ratio of hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 1.6-2.2: 0.4-0.6: 0.01-0.02: 40-60. In the above reaction process, anhydrous DMF is used as solvent, phosphotungstic acid is used as catalyst, hydroxy boron nitride and 3,5-diaminobenzoic acid undergo esterification reaction to obtain functional components. In the above reaction process, the amount of hydroxyl monomer is controlled to be slightly higher than that of 2-mercaptonicotinic acid, so that after the reaction, there are still remaining hydroxyl groups that can participate in the subsequent preparation process.

[0013] Preferably, the modified thermally conductive filler is prepared by the following steps: Step B1, under nitrogen protection, adding nano hexagonal boron nitride to an alkaline solution, heating to 106-112° C., stirring and reacting for 36-42 hours, and after the reaction is completed, precipitating, washing, and drying to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to the alkaline solution is 3-5:600-700; Step B2, hydroxyboron nitride, 3,5-Diaminobenzoic acid and p-toluenesulfonic acid are added to anhydrous DMF, stirred evenly, heated to 78-84°C under nitrogen protection, stirred for reaction for 12-16h, and after the reaction is completed, filtered, washed, and dried to obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.2-2.6:15.2-18.4:0.14-0.20:70-78. In the above reaction process, anhydrous DMF is used as solvent and p-toluenesulfonic acid is used as catalyst, and hydroxyboron nitride and 3,5-diaminobenzoic acid undergo esterification reaction to obtain an amino monomer. In the above reaction process, the amount of hydroxyboron nitride is controlled to be slightly higher than 3,5-diaminobenzoic acid, so that after the reaction is completed, there are still remaining hydroxyl groups that can participate in the subsequent preparation process; Step B3, add the amino monomer to anhydrous DMF, stir evenly, adjust the pH value to 8-9, add a mixed solution b of octenyl succinic anhydride and isopropanol dropwise, and control the dripping to be completed within 10 minutes. After the dripping is completed, heat to 72-76°C, continue stirring and reacting for 6-12 hours, then adjust the pH value to 6.4-6.8, wash, and dry to obtain a modified thermally conductive filler, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 3-5:62-66:32-36, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution b is 4-6.8:28. In the above reaction process, anhydrous DMF is used as a solvent, and the active amino group on the amino monomer undergoes a ring-opening esterification reaction with the anhydride on the octenyl succinic anhydride to obtain a modified thermally conductive filler.

[0014] Preferably, in step B1, the alkaline solution is a sodium hydroxide aqueous solution with a mass fraction of 30-40%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: In order to improve the thermal conductivity and insulation of the aluminum-based copper-clad laminate, the present application starts from two aspects. First, a functional component is added in the process of preparing the thermal conductive adhesive. The functional component contains a microcrystalline cellulose structure, a ricinoleate structure and a pyridine group. The presence of the microcrystalline cellulose structure, on the one hand, exerts its own high crystallinity and orientation, thereby improving the thermal conductivity and insulation of the aluminum-based copper-clad laminate. On the other hand, it can form hydrogen bonds with the active carboxyl groups on the modified thermal conductive filler, thereby improving the dispersibility of the modified thermal conductive filler and further improving the thermal conductivity of the aluminum-based copper-clad laminate. The ricinoleate structure has orderliness, thereby improving the thermal conductivity of the aluminum-based copper-clad laminate. The thermal conductivity and insulation of the board are improved. The presence of pyridine can produce π-π interaction with the benzene ring on the modified thermal conductive filler, realize the loading of functional components on the surface of the modified thermal conductive filler, and further improve the thermal conductivity and insulation of the aluminum-based copper clad laminate. Secondly, the addition of modified thermal conductive fillers, on the one hand, brings into play the good thermal conductivity of boron nitride itself, on the other hand, the octenyl succinic anhydride grafted on the surface of the modified thermal conductive filler contains unsaturated double bonds, which can chemically bond with the thiol group on the functional component. Introducing it into the thermal conductive adhesive can synergize with the functional component to jointly improve the thermal conductivity and insulation of the aluminum-based copper clad laminate. DETAILED DESCRIPTION

[0016] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.

[0017] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0018] Preparation Examples 1-3 and Comparative Preparation Examples 1-2 provide preparation methods of functional components.

[0019] Preparation Example 1 This preparation example provides a method for preparing a functional component, and the method for preparing the functional component comprises the following steps: Step A1, stirring microcrystalline cellulose and saturated sodium hydroxide solution at a speed of 500 rpm for 16 minutes until uniform, then adding epichlorohydrin, heating to 58°C, maintaining the speed unchanged, continuing stirring for 5.2 hours, filtering, and then adding a mixed solution a of ricinoleic acid, pyridine and anhydrous DMF dropwise, controlling the dripping to be completed within 30 minutes, heating to 76°C, and continuing the reaction for 4 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60°C to constant weight to obtain a hydroxyl monomer, wherein the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 0.6:64:2.4:32, and the mass ratio of ricinoleic acid, pyridine and anhydrous DMF in the mixed solution a is 4:0.03:28; Step A2, adding hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid to anhydrous DMF, stirring at a rotation speed of 650 rpm for 18 minutes until uniform, heating to 74°C under nitrogen protection, stirring and reacting for 9 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 68°C to constant weight to obtain functional components, wherein the mass ratio of hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 1.6:0.4:0.01:40.

[0020] Preparation Example 2 This preparation example provides a method for preparing a functional component, and the method for preparing the functional component comprises the following steps: Step A1, stirring microcrystalline cellulose and saturated sodium hydroxide solution at a rotation speed of 550 rpm for 20 minutes until uniform, then adding epichlorohydrin, heating to 61°C, continuing stirring for 5.8 hours, filtering, and then adding a mixed solution a of ricinoleic acid, pyridine and anhydrous DMF, and controlling the dripping to be completed within 30 minutes. After the dripping is completed, the temperature is raised to 79°C, and the reaction is continued for 5 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 64°C to constant weight to obtain a hydroxyl monomer, wherein the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 0.8:70:2.7:33, and the mass ratio of ricinoleic acid, pyridine and anhydrous DMF in the mixed solution a is 4:0.04:29; Step A2, adding hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid to anhydrous DMF, stirring at a speed of 700 rpm for 22 minutes until uniform, heating to 77°C under nitrogen protection, maintaining the speed unchanged, stirring and reacting for 10.5 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 72°C to constant weight to obtain functional components, wherein the mass ratio of hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 1.9:0.5:0.015:50.

[0021] Preparation Example 3 This preparation example provides a method for preparing a functional component, and the method for preparing the functional component comprises the following steps: Step A1, stirring microcrystalline cellulose and saturated sodium hydroxide solution at a speed of 600 rpm for 24 minutes until uniform, then adding epichlorohydrin, heating to 64°C, maintaining the speed unchanged, continuing stirring for 6.4 hours, filtering, and then adding a mixed solution a of ricinoleic acid, pyridine and anhydrous DMF dropwise, controlling the dripping to be completed within 30 minutes, and after the dripping is completed, heating to 82°C, and continuing the reaction for 6 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 68°C to constant weight to obtain a hydroxyl monomer, wherein the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 1.0:76:3.0:34, and the mass ratio of ricinoleic acid, pyridine and anhydrous DMF in the mixed solution a is 4:0.05:30; Step A2, adding hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid to anhydrous DMF, stirring at a rotation speed of 750 rpm for 26 minutes until uniform, heating to 80°C under nitrogen protection, stirring and reacting for 12 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 76°C to constant weight to obtain functional components, wherein the mass ratio of hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 2.2:0.6:0.02:60.

[0022] Comparative Preparation Example 1 This comparative preparation example provides a method for preparing a functional component, and the method for preparing the functional component comprises the following steps: Step A1, stirring microcrystalline cellulose and saturated sodium hydroxide solution at a speed of 500 rpm for 16 minutes until uniform, then adding epichlorohydrin, heating to 58°C, maintaining the speed unchanged, continuing stirring for 5.2 hours, filtering, and then adding a mixture of octanoic acid, pyridine and anhydrous DMF dropwise, and controlling the dripping to be completed within 30 minutes. After the dripping is completed, the temperature is raised to 76°C and the reaction is continued for 4 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60°C to constant weight to obtain a hydroxyl monomer, wherein the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 0.6:64:2.4:32, and the mass ratio of octanoic acid, pyridine and anhydrous DMF in the mixed solution a is 4:0.03:28; Step A2, adding hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid to anhydrous DMF, stirring at a rotation speed of 650 rpm for 18 minutes until uniform, heating to 74°C under nitrogen protection, stirring and reacting for 9 hours, after the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 68°C to constant weight to obtain functional components, wherein the mass ratio of hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 1.6:0.4:0.01:40.

[0023] Comparative Preparation Example 2 This comparative preparation example provides a method for preparing a functional component, and the method for preparing the functional component comprises the following steps: Step A1, stirring microcrystalline cellulose and saturated sodium hydroxide solution at a speed of 500 rpm for 16 minutes until uniform, then adding epichlorohydrin, heating to 58°C, maintaining the speed unchanged, continuing stirring for 5.2 hours, filtering, and then adding a mixed solution a of ricinoleic acid, pyridine and anhydrous DMF dropwise, controlling the dripping to be completed within 30 minutes, heating to 76°C, and continuing the reaction for 4 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 60°C to constant weight to obtain a hydroxyl monomer, wherein the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 0.6:64:2.4:32, and the mass ratio of ricinoleic acid, pyridine and anhydrous DMF in the mixed solution a is 4:0.03:28; Step A2, add hydroxyl monomer, 3-mercaptopropionic acid and phosphotungstic acid to anhydrous DMF, stir at a speed of 650 rpm for 18 minutes until uniform, heat to 74°C under nitrogen protection, stir and react for 9 hours, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water three times in sequence, and dry at 68°C to constant weight to obtain functional components, wherein the mass ratio of hydroxyl monomer, 3-mercaptopropionic acid, phosphotungstic acid and anhydrous DMF is 1.6:0.4:0.01:40.

[0024] Preparation Examples 4-6 and Comparative Preparation Examples 3-4 provide methods for preparing modified thermally conductive fillers.

[0025] Preparation Example 4 This preparation example provides a modified thermally conductive filler, which is prepared by the following steps: Step B1, under nitrogen protection, adding nano hexagonal boron nitride to a 30% sodium hydroxide aqueous solution by mass, heating to 106°C, controlling the rotation speed to 400rpm, stirring and reacting for 36h, after the reaction is completed, precipitating, washing with anhydrous methanol for 3 times, and drying at 60°C to constant weight to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to sodium hydroxide solution is 3:600; Step B2, add hydroxyboron nitride, 3,5-diaminobenzoic acid and p-toluenesulfonic acid to anhydrous DMF, control the speed to 600rpm, stir for 26min until uniform, heat to 78°C under nitrogen protection, maintain the speed unchanged, continue stirring to react for 12h, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water for 3 times, dry at 65°C to constant weight, and obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.2:15.2:0.14:70; Step B3, add the amino monomer to anhydrous DMF, stir at a speed of 700 rpm for 22 minutes until uniform, adjust the pH value to 8 with 0.6M sodium hydroxide aqueous solution, add a mixed solution b of octenyl succinic anhydride and isopropanol, and control the dripping within 10 minutes. After the dripping is completed, the temperature is raised to 72°C, the speed is maintained unchanged, and the stirring reaction is continued for 6 hours. Then, the pH value is adjusted to 6.4 with 0.4M hydrochloric acid solution, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 68°C to constant weight to obtain a modified thermal conductive filler, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 3:62:32, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution b is 4:28.

[0026] Preparation Example 5 This preparation example provides a modified thermally conductive filler, which is prepared by the following steps: Step B1, under nitrogen protection, adding nano hexagonal boron nitride to a sodium hydroxide aqueous solution with a mass fraction of 35%, heating to 109°C, controlling the rotation speed to 450rpm, stirring and reacting for 39h, after the reaction is completed, precipitating, washing with anhydrous methanol 4 times, and drying at 60°C to constant weight to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to sodium hydroxide solution is 4:650; Step B2, adding hydroxyboron nitride, 3,5-diaminobenzoic acid and p-toluenesulfonic acid to anhydrous DMF, controlling the rotation speed to 650rpm, stirring for 28min until uniform, heating to 81°C under nitrogen protection, stirring and reacting for 14h, after the reaction is completed, filtering, and then washing with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 70°C to constant weight to obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.4:16.8:0.17:74; Step B3, add the amino monomer to anhydrous DMF, stir at a speed of 720rpm for 24min until uniform, adjust the pH value to 8.5 with 0.8M sodium hydroxide aqueous solution, add dropwise a mixed solution b of octenyl succinic anhydride and isopropanol, and control the dripping to be completed within 10min. After the dripping is completed, the temperature is raised to 74°C, the speed is maintained unchanged, and the stirring reaction is continued for 9h, and then the pH value is adjusted to 6.6 with 0.4M hydrochloric acid solution, and then washed with anhydrous ethanol and deionized water for 4 times in sequence, and dried at 72°C to constant weight to obtain a modified thermal conductive filler, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 4:64:34, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution b is 4.9:28.

[0027] Preparation Example 6 This preparation example provides a modified thermally conductive filler, which is prepared by the following steps: Step B1, under nitrogen protection, add nano hexagonal boron nitride to a sodium hydroxide aqueous solution with a mass fraction of 40%, heat to 112°C, control the rotation speed to 500rpm, stir and react for 42h, after the reaction is completed, precipitate, wash with anhydrous methanol 5 times, and dry at 65°C to constant weight to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to sodium hydroxide solution is 5:700; Step B2, adding hydroxyboron nitride, 3,5-diaminobenzoic acid and p-toluenesulfonic acid to anhydrous DMF, controlling the rotation speed to 650rpm, stirring for 30min until uniform, heating to 84°C under nitrogen protection, stirring and reacting for 16h, after the reaction is completed, filtering, and then washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 75°C to constant weight to obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.6:18.4:0.20:78; Step B3, add the amino monomer to anhydrous DMF, stir at a speed of 740rpm for 26min until uniform, adjust the pH value to 9, add dropwise a mixed solution b of octenyl succinic anhydride and isopropanol, and control the dripping to be completed within 10min. After the dripping is completed, heat to 76°C, continue stirring to react for 12h, then adjust the pH value to 6.8, and then wash with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 76°C to constant weight to obtain a modified thermal conductive filler, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 5:66:36, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution b is 6.8:28.

[0028] Comparative Preparation Example 3 This comparative preparation example provides a modified thermally conductive filler, which is prepared by the following steps: Step B1, under nitrogen protection, adding nano hexagonal boron nitride to a 30% sodium hydroxide aqueous solution by mass, heating to 106°C, controlling the rotation speed to 400rpm, stirring and reacting for 36h, after the reaction is completed, precipitating, washing with anhydrous methanol for 3 times, and drying at 60°C to constant weight to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to sodium hydroxide solution is 3:600; Step B2, adding hydroxyboron nitride, L-cystine and p-toluenesulfonic acid to anhydrous DMF, controlling the rotation speed to 600 rpm, stirring for 26 minutes until uniform, heating to 78°C under nitrogen protection, maintaining the rotation speed unchanged, and continuing to stir and react for 12 hours. After the reaction is completed, filtering, washing with anhydrous ethanol and deionized water for 3 times, and drying at 65°C to constant weight to obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, L-cystine, p-toluenesulfonic acid and anhydrous DMF is 2.2:15.2:0.14:70; Step B3, add the amino monomer to anhydrous DMF, stir at a speed of 700 rpm for 22 minutes until uniform, adjust the pH value to 8 with 0.6M sodium hydroxide aqueous solution, add a mixed solution b of octenyl succinic anhydride and isopropanol, and control the dripping within 10 minutes. After the dripping is completed, the temperature is raised to 72°C, the speed is maintained unchanged, and the stirring reaction is continued for 6 hours. Then, the pH value is adjusted to 6.4 with 0.4M hydrochloric acid solution, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 68°C to constant weight to obtain a modified thermal conductive filler, wherein the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 3:62:32, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution b is 4:28.

[0029] Comparative Preparation Example 4 This comparative preparation example provides a modified thermally conductive filler, which is prepared by the following steps: A method for preparing a modified thermally conductive filler, wherein the modified thermally conductive filler is prepared by the following steps: Step B1, under nitrogen protection, adding nano hexagonal boron nitride to a 30% sodium hydroxide aqueous solution by mass, heating to 106°C, controlling the rotation speed to 400rpm, stirring and reacting for 36h, after the reaction is completed, precipitating, washing with anhydrous methanol for 3 times, and drying at 60°C to constant weight to obtain hydroxyboron nitride, wherein the mass ratio of nano hexagonal boron nitride to sodium hydroxide solution is 3:600; Step B2, add hydroxyboron nitride, 3,5-diaminobenzoic acid and p-toluenesulfonic acid to anhydrous DMF, control the speed to 600rpm, stir for 26min until uniform, heat to 78°C under nitrogen protection, maintain the speed unchanged, continue stirring to react for 12h, after the reaction is completed, filter, wash with anhydrous ethanol and deionized water for 3 times, dry at 65°C to constant weight, and obtain an amino monomer, wherein the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.2:15.2:0.14:70; Step B3, add the amino monomer to anhydrous DMF, stir at a speed of 700 rpm for 22 minutes until uniform, adjust the pH value to 8 with 0.6M sodium hydroxide aqueous solution, add a mixed solution b of n-octyl succinic anhydride and isopropanol, and control the dripping within 10 minutes. After the dripping is completed, the temperature is raised to 72°C, the speed is maintained unchanged, and the stirring reaction is continued for 6 hours, and then the pH value is adjusted to 6.4 with 0.4M hydrochloric acid solution, and then washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 68°C to constant weight to obtain a modified thermal conductive filler, wherein the mass ratio of amino monomer, anhydrous DMF and mixed solution b is 3:62:32, and the mass ratio of n-octyl succinic anhydride and isopropanol in the mixed solution b is 4:28.

[0030] Preparation Examples 7-9 and Comparative Preparation Examples 5-8 provide a method for preparing a thermally conductive adhesive.

[0031] Preparation Example 7 This preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 64 parts of bisphenol A epoxy resin, 16 parts of the functional component prepared in Preparation Example 1, 8 parts of the modified thermal conductive filler prepared in Preparation Example 4, 20 parts of propylene glycol methyl ether, 0.1 parts of benzoin dimethyl ether, 25 parts of epoxy resin curing agent T31, and 1 part of 1-benzylbenzene-2-ethylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to propylene glycol methyl ether, stirred at a rotation speed of 600 rpm for 25 minutes until uniform, the rotation speed was maintained unchanged, and placed under ultraviolet irradiation for 10 minutes while stirring, and the irradiation temperature was controlled at 50°C, then cooled to 25°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-benzylbenzene-2-ethylimidazole were added in sequence, and the emulsification reaction was carried out at a rotation speed of 1000 rpm for 1.6 hours, and the mixture was allowed to stand for 5 hours to obtain a thermal conductive adhesive liquid.

[0032] Preparation Example 8 This preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 98 parts of bisphenol A epoxy resin, 23 parts of the functional component prepared in Preparation Example 2, 13 parts of the modified thermal conductive filler prepared in Preparation Example 5, 30 parts of propylene glycol methyl ether acetate, 0.15 parts of benzoin dimethyl ether, 27.5 parts of epoxy resin curing agent T31, and 3 parts of 2-ethyl-4-methylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether are added to propylene glycol methyl ether acetate, stirred at a rotation speed of 640 rpm for 28 minutes until uniform, the rotation speed is maintained unchanged, and placed under ultraviolet irradiation for 12.5 minutes while stirring, and the irradiation temperature is controlled at 53°C, cooled to 28°C, and then bisphenol A type epoxy resin, epoxy resin curing agent T31 and 2-ethyl-4-methylimidazole are added in sequence, emulsified at a rotation speed of 1100 rpm for 2.2 hours, and allowed to stand for 6 hours to obtain a thermal conductive adhesive liquid.

[0033] Preparation Example 9 This preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 132 parts of bisphenol A epoxy resin, 30 parts of the functional component prepared in Preparation Example 3, 18 parts of the modified thermal conductive filler prepared in Preparation Example 6, 40 parts of cyclohexanone, 0.2 parts of benzoin dimethyl ether, 30 parts of epoxy resin curing agent T31, and 5 parts of 1-cyanoethyl imidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to cyclohexanone, stirred at a rotation speed of 680 rpm for 31 minutes until uniform, the rotation speed was maintained constant, and placed under ultraviolet irradiation for 15 minutes while stirring, and the irradiation temperature was controlled at 56°C, then cooled to 30°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-cyanoethylimidazole were added in sequence, emulsified at a rotation speed of 1200 rpm for 2.8 hours, and allowed to stand for 7 hours to obtain a thermal conductive adhesive liquid.

[0034] Comparative Preparation Example 5 This comparative preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 64 parts of bisphenol A epoxy resin, 16 parts of the functional component prepared in Comparative Preparation Example 1, 8 parts of the modified thermal conductive filler prepared in Preparation Example 4, 20 parts of propylene glycol methyl ether, 0.1 parts of benzoin dimethyl ether, 25 parts of epoxy resin curing agent T31, and 1 part of 1-benzylbenzene-2-ethylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to propylene glycol methyl ether, stirred at a rotation speed of 600 rpm for 25 minutes until uniform, the rotation speed was maintained unchanged, and placed under ultraviolet irradiation for 10 minutes while stirring, and the irradiation temperature was controlled at 50°C, then cooled to 25°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-benzylbenzene-2-ethylimidazole were added in sequence, and the emulsification reaction was carried out at a rotation speed of 1000 rpm for 1.6 hours, and the mixture was allowed to stand for 5 hours to obtain a thermal conductive adhesive liquid.

[0035] Comparative Preparation Example 6 This comparative preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 64 parts of bisphenol A epoxy resin, 16 parts of the functional component prepared in Comparative Preparation Example 2, 8 parts of the modified thermal conductive filler prepared in Preparation Example 4, 20 parts of propylene glycol methyl ether, 0.1 parts of benzoin dimethyl ether, 25 parts of epoxy resin curing agent T31, and 1 part of 1-benzylbenzene-2-ethylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to propylene glycol methyl ether, stirred at a rotation speed of 600 rpm for 25 minutes until uniform, the rotation speed was maintained unchanged, and placed under ultraviolet irradiation for 10 minutes while stirring, and the irradiation temperature was controlled at 50°C, then cooled to 25°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-benzylbenzene-2-ethylimidazole were added in sequence, and the emulsification reaction was carried out at a rotation speed of 1000 rpm for 1.6 hours, and the mixture was allowed to stand for 5 hours to obtain a thermal conductive adhesive liquid.

[0036] Comparative Preparation Example 7 This comparative preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 64 parts of bisphenol A epoxy resin, 16 parts of the functional component prepared in Preparation Example 1, 8 parts of the modified thermal conductive filler prepared in Comparative Preparation Example 3, 20 parts of propylene glycol methyl ether, 0.1 parts of benzoin dimethyl ether, 25 parts of epoxy resin curing agent T31, and 1 part of 1-benzylbenzene-2-ethylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to propylene glycol methyl ether, stirred at a rotation speed of 600 rpm for 25 minutes until uniform, the rotation speed was maintained unchanged, and placed under ultraviolet irradiation for 10 minutes while stirring, and the irradiation temperature was controlled at 50°C, then cooled to 25°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-benzylbenzene-2-ethylimidazole were added in sequence, and the emulsification reaction was carried out at a rotation speed of 1000 rpm for 1.6 hours, and the mixture was allowed to stand for 5 hours to obtain a thermal conductive adhesive liquid.

[0037] Comparative Preparation Example 8 This comparative preparation example provides a method for preparing a thermally conductive adhesive liquid, and the method for preparing the thermally conductive adhesive liquid comprises the following steps: Step 1: Prepare the following raw materials in parts by weight: 64 parts of bisphenol A epoxy resin, 16 parts of the functional component prepared in Preparation Example 1, 8 parts of the modified thermal conductive filler prepared in Comparative Preparation Example 4, 20 parts of propylene glycol methyl ether, 0.1 parts of benzoin dimethyl ether, 25 parts of epoxy resin curing agent T31, and 1 part of 1-benzylbenzene-2-ethylimidazole; In the second step, the functional components, modified thermal conductive filler and benzoin dimethyl ether were added to propylene glycol methyl ether, stirred at a rotation speed of 600 rpm for 25 minutes until uniform, the rotation speed was maintained unchanged, and placed under ultraviolet irradiation for 10 minutes while stirring, and the irradiation temperature was controlled at 50°C, then cooled to 25°C, and bisphenol A type epoxy resin, epoxy resin curing agent T31 and 1-benzylbenzene-2-ethylimidazole were added in sequence, and the emulsification reaction was carried out at a rotation speed of 1000 rpm for 1.6 hours, and the mixture was allowed to stand for 5 hours to obtain a thermal conductive adhesive liquid.

[0038] Examples 1-3 and Comparative Examples 1-4 provide a method for preparing a high thermal conductivity aluminum-based copper-clad laminate.

[0039] Example 1 Step S1, coating the thermally conductive adhesive prepared in Preparation Example 7 on the copper foil, controlling the gluing line speed to 12 m / min, controlling the coating thickness to 75 μm, and heat treating at 230° C. for 2 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20 MPa and 280° C. for 1.8 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0040] Example 2 This embodiment provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum substrate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in Preparation Example 8 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermal conductive adhesive prepared in Preparation Example 8 on the copper foil, controlling the gluing line speed to 16 m / min, controlling the coating thickness to 85 μm, and heat treating at 245° C. for 3 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 23 MPa and 300° C. for 1.8-2.2 h, and cooling to obtain a high thermal conductivity aluminum-based copper-clad laminate.

[0041] Example 3 This embodiment provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum base plate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in Preparation Example 9 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermally conductive adhesive prepared in Preparation Example 9 on the copper foil, controlling the gluing line speed to 20 m / min, controlling the coating thickness to 95 μm, and heat treating at 260° C. for 4 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 25 MPa and 320° C. for 2.2 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0042] Comparative Example 1 This comparative example provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum base plate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in comparative preparation example 5 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermally conductive adhesive prepared in Comparative Preparation Example 5 on the copper foil, controlling the gluing line speed to 12 m / min, controlling the coating thickness to 75 μm, and heat treating at 230° C. for 2 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20 MPa and 280° C. for 1.8 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0043] Comparative Example 2 This comparative example provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum substrate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in comparative preparation example 6 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermally conductive adhesive prepared in Comparative Preparation Example 6 on the copper foil, controlling the gluing line speed to 12 m / min, controlling the coating thickness to 75 μm, and heat treating at 230° C. for 2 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20 MPa and 280° C. for 1.8 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0044] Comparative Example 3 This comparative example provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum base plate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in comparative preparation example 7 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermally conductive adhesive prepared in Comparative Preparation Example 7 on the copper foil, controlling the gluing line speed to 12 m / min, controlling the coating thickness to 75 μm, and heat treating at 230° C. for 2 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20 MPa and 280° C. for 1.8 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0045] Comparative Example 4 This comparative example provides a high thermal conductivity aluminum-based copper-clad laminate, including an aluminum base plate and a prepreg, wherein the prepreg is prepared by thermally curing the thermal conductive adhesive prepared in comparative preparation example 8 and copper foil; The method for preparing the high thermal conductivity aluminum-based copper-clad laminate comprises the following steps: Step S1, coating the thermally conductive adhesive prepared in Comparative Preparation Example 8 on the copper foil, controlling the gluing line speed to 12 m / min, controlling the coating thickness to 75 μm, and heat treating at 230° C. for 2 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20 MPa and 280° C. for 1.8 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

[0046] Performance Testing The thermal conductivity and breakdown voltage resistance of the aluminum-based copper-clad laminates prepared in Examples 1-3 and Comparative Examples 1-4 were tested. The thermal conductivity test method was ASTM D5470, and the breakdown voltage resistance test method was IPC-TM-6502.5.6. The test results are shown in Table 1 below: Table 1 Thermal conductivity and insulation test of aluminum-based copper-clad laminates prepared in Examples 1-3 and Comparative Examples 1-4 It can be seen from Table 1 that, compared with Comparative Examples 1-4, the aluminum-based copper-clad laminates prepared in Examples 1-3 have better thermal conductivity and insulation.

[0047] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high thermal conductivity aluminum-based copper-clad laminate, characterized in that: It includes an aluminum base plate and a prepreg, wherein the prepreg is made by thermally curing a thermally conductive adhesive and a copper foil; The thermal conductive adhesive is prepared by firstly performing click addition reaction on the functional component and the modified thermal conductive filler, and then chemically cross-linking with the epoxy resin; The functional component is firstly prepared by treating microcrystalline cellulose with a saturated aqueous solution of hydrogen peroxide, then reacting with epichlorohydrin through a nucleophilic substitution reaction, then reacting with ricinoleic acid through a ring-opening esterification reaction to obtain a hydroxyl monomer, and finally reacting with 2-mercaptonicotinic acid through an esterification reaction; The modified thermal conductive filler is first treated with an alkaline solution to obtain hydroxyboron nitride, and then 3,5-Diaminobenzoic acid The amino monomer is obtained by esterification reaction, and finally the monomer is obtained by ring-opening esterification reaction with octenyl succinic anhydride.

2. The high thermal conductivity aluminum-based copper-clad laminate according to claim 1, characterized in that: The preparation method of the thermal conductive adhesive comprises the following steps: Step 1: prepare the following raw materials by weight: 64-132 parts of bisphenol A epoxy resin, 16-30 parts of functional components, 8-18 parts of modified thermal conductive filler, 20-40 parts of organic solvent, 0.1-0.2 parts of photoinitiator, 25-30 parts of curing agent, and 1-5 parts of curing accelerator; The second step is to add the functional components, modified thermal conductive filler and photoinitiator into the organic solvent, stir evenly, irradiate with ultraviolet light for 10-20 minutes, control the irradiation temperature at 50-56°C, cool down to 25-30°C, and then add bisphenol A type epoxy resin, curing agent and curing accelerator in sequence, emulsify for 1.6-2.8 hours, and let stand for 5-7 hours to obtain the thermal conductive adhesive liquid.

3. The high thermal conductivity aluminum-based copper-clad laminate according to claim 2, characterized in that: The preparation method of the functional component comprises the following steps: Step A1, mix microcrystalline cellulose and saturated sodium hydroxide solution evenly, then add epichlorohydrin, heat to 58-64°C, continue stirring for 5.2-6.4h, filter, then add a mixture of ricinoleic acid, pyridine and anhydrous DMF dropwise, control the dripping to be completed within 30min, heat to 76-82°C, continue the reaction for 4-6h, filter, wash and dry after the reaction is completed to obtain a hydroxyl monomer; Step A2, add hydroxyl monomer, 2-mercaptonicotinic acid and phosphotungstic acid into anhydrous DMF, stir evenly, raise the temperature to 74-80° C. under nitrogen protection, stir and react for 9-12 hours, after the reaction is completed, filter, wash and dry to obtain functional components.

4. The high thermal conductivity aluminum-based copper-clad laminate according to claim 3, characterized in that: In the step A1, the mass ratio of microcrystalline cellulose, saturated sodium hydroxide solution, epichlorohydrin and mixed solution a is 0.6-1.0:64-76:2.4-3.0:32-34, and in the mixed solution a, the mass ratio of ricinoleic acid, pyridine and anhydrous DMF is 4:0.03-0.05:28-30.

5. The high thermal conductivity aluminum-based copper-clad laminate according to claim 3, characterized in that: In the step A2, the mass ratio of the hydroxyl monomer, 2-mercaptonicotinic acid, phosphotungstic acid and anhydrous DMF is 1.6-2.2: 0.4-0.6: 0.01-0.02: 40-60.

6. The high thermal conductivity aluminum-based copper-clad laminate according to claim 1, characterized in that: The modified thermally conductive filler is prepared by the following steps: Step B1, under nitrogen protection, add nano hexagonal boron nitride to an alkaline solution, heat to 106-112°C, stir and react for 36-42 hours, and after the reaction is completed, precipitate, wash and dry to obtain hydroxyboron nitride; Step B2, adding hydroxyboron nitride, 3,5-diaminobenzoic acid and p-toluenesulfonic acid to anhydrous DMF, stirring evenly, heating to 78-84° C. under nitrogen protection, stirring for reaction for 12-16 hours, and after the reaction is completed, filtering, washing and drying to obtain an amino monomer; Step B3, add the amino monomer to anhydrous DMF, stir evenly, adjust the pH value to 8-9, add dropwise a mixture of octenyl succinic anhydride and isopropanol b, and control the dripping to be completed within 10 minutes. After the dripping is completed, heat to 72-76°C, continue stirring and reacting for 6-12 hours, then adjust the pH value to 6.4-6.8, wash, and dry to obtain a modified thermal conductive filler.

7. The high thermal conductivity aluminum-based copper-clad laminate according to claim 6, characterized in that: In the step B1, the mass ratio of nano hexagonal boron nitride to the alkaline solution is 3-5:600-700.

8. The high thermal conductivity aluminum-based copper-clad laminate according to claim 6, characterized in that: In the step B2, the mass ratio of hydroxyboron nitride, 3,5-diaminobenzoic acid, p-toluenesulfonic acid and anhydrous DMF is 2.2-2.6:15.2-18.4:0.14-0.20:70-78.

9. The high thermal conductivity aluminum-based copper-clad laminate according to claim 6, characterized in that: In the step B3, the mass ratio of the amino monomer, anhydrous DMF and the mixed solution b is 3-5:62-66:32-36, and in the mixed solution b, the mass ratio of octenyl succinic anhydride and isopropanol is 4-6.8:

28.

10. A method for preparing a high thermal conductivity aluminum-based copper-clad laminate according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, coating the thermal conductive adhesive on the copper foil, controlling the adhesive coating line speed to 12-20 m / min, controlling the coating thickness to 75-95 μm, and heat treating at 230-260° C. for 2-4 min to obtain a prepreg; Step S2, cutting the prepreg and superimposing it with the aluminum base plate, hot pressing at 20-25 MPa and 280-320° C. for 1.8-2.2 h, and cooling to obtain a high thermal conductivity aluminum-based copper clad laminate.

Citation Information

Patent Citations

  • Aluminum-based copper-clad plate with high voltage resistance and high thermal conductivity

    CN113290976A

  • Heat-conducting silicone rubber material and preparation method thereof

    CN118878992A

  • Thermosetting resin composition for degradable heat-conducting aluminum-based copper-clad plate, heat-conducting aluminum-based copper-clad plate, and preparation method and recovery method thereof

    WO2016090859A1